Lina Bo Bardi's Curatorial and Architectural Combativeness - Vicentin, Pedro Santos Pavioti (Revista do Colóquio, 2024)
This article explores the combative nature of Lina Bo Bardi's work through her conception of architecture, curating and reception as means of intervening in the social fabric and bringing about change. Based on the exhibition "A Mão do Povo Brasileiro" (The Hand of the Brazilian People) at MASP as the main case study of her work as a curator, this article seeks to reflect on the processes of disruptive propositions instilled not only in her conceptions of architecture and curatorship, but also in her work at the Oficina Theatre and the autonomy she sought to confer on the public visiting these exhibition spaces.